Who is Rolf Italiaander? = Qui est Rolf Intaliaander? - Frenzel, Christian Otto (Hamburg : Freie Akademie der Künste in Hamburg, 1963)
Bibliotheek Camille Huysmans
Separata: "Unterwegs mit Rolf Italiaander"
Engels
Frans
Brochure